Duodenal-Distal Ileal Fistula After Laparoscopic Radical Right Hemicolectomy: A Case Report - You, Xiaolan; Zhao, Xiaojun; Huang, Chuanjiang; Cheng, Zhiyi; Liu, Guiyuan; Shen, Xianhe; Zheng, Tingrui (Frontiers in Surgery, 2022)
Right hemicolectomy for colon cancer may be complicated by leaks, stenoses, or fistulas. These complications usually occur at the ileocolic anastomosis and can be managed endoscopically. However, fistulas that are large cannot be managed by endoscopy and require surgical intervention. After laparoscopic radical right hemicolectomy, duodenal fistulae is relatively rare. Among duodenal fistulae, internal duodenocolic fistulae is relatively common, but duodeno-ileum fistulae is extremely rare. Here, we report a case of duodeno-distal ileum fistula after right hemicolectomy with short bowel syndrome, that was surgically treated. After surgical treatment, the symptoms of short bowel syndrome disappeared, weight gain was obvious, and the clinical effect was satisfactory.